The Effect of Substitution of Red Rice Flour (Oryza nivara) With Addition of Banana (Musa paradisiaca L.) on the Physical and Chemical Properties of Almond Crispy - Luthfi, Ageng Dwi; Pury Artha, Bareta Agdia (Food Scientia: Journal of Food Science and Technology, 2021)
Banana is a nutritious food and is a source of carbohydrates, vitamins and minerals. Brown rice is a food ingredient that is rich in anthocyanins. One of the simplest brown rice processing is the manufacturing of brown rice flour. The use and utilization of bananas and brown rice flour as a substitute for food processing can be realized by industries engaged in the food sector, one of which is the bakery industry. This research purpose is to produce cookie products, namely almond crispy with banana and red rice flour substitution. The experimental design used is a completely randomized design with the first factor being the ratio of brown rice flour and bananas (80%: 20%; 70%: 30%; 60%: 40%). The second factor is the type of banana (Milk Banana, Ambon Banana, Kepok Banana). The results shows the highest water content is from the formulation of 60% brown rice flour and 40% Kepok Banana (3,74%), the highest ash level is from the formulation of 80% brown rice flour and 20% banana milk (3,85%) and the highest antioxidant activity is from the formulation with 70% brown rice flour and 30% banana milk (16,80%).